Effect of Melia Azedarach Extract on Some Selected Physiological Parameters of (Catla catla) - S Rajeshwari; MK Rajan; M Pavaraj; SP Sevarkodiyone (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2016)
The present study has been carried out the effect of leaf extract of Melia azedarach at different concentration, such as 1.0g, 1.5g and 2.0g formulated diet against 0.1 ml of CFU/ ml 105 cells Aeromonas hydrophila on catla catla. The physiological parameters, such as Survival and Mortality, Antibody response, Phagocytic activity, Oxygen consumption, opercular movement, and Growth rate were studied. Result revealed that control fish showed 60% mortality and 20%, mortality at 1.0g concentration of plant extract, 10% mortality at 1.5g concentration of plant extract 30% mortality at 2.0g concentration of plant extract was observed. The maximum level of physiological activity Survival and Mortality, Antibody response, Phagocytic activity, Oxygen consumption, opercular movement, and Growth rate was recorded at 1.5g of plant extract formulated diet treated fish. When compared with control, However physiological parameters was significantly (p<0.05) increased when compared with control.